A Systematic Review and Meta-analysis of Using Acupuncture and Acupressure for Uremic Pruritus (Iranian Journal of Kidney Diseases, 2018)
Introduction. Uremic pruritus is characterized by an uncomfortable and unlimited sensation which leads to scratch, which strongly reduces the quality of life. Pruritus is a common symptom in patients with end-stage renal disease. Various clinical trial studies have examined the effects of acupuncture and acupressure on treatment of uremic pruritus. This systematic review meta-analysis aimed to evaluate the effectiveness based on published studies. Materials and Methods. An electronic literature search was conducted to identify appropriate trial studies. The results for continuous outcomes were presented as weighted mean difference, with 95% confidence intervals. Results. A total of 5 articles, including 6 trials, were enrolled in this systematic review. Only 3 of the six trial studies used a visual analogue scale score for assessing pruritus and acupressure for intervention regime, which were considered for meta-analysis. The combined results showed that acupuncture or acupressure was effective in treatment of uremic pruritus (pooled mean difference, -1.994; 95% confidence interval, -2.544 to -1.445). Conclusions. This study confirms that using acupuncture and acupressure is effective in treatment of uremic pruritus. However, further vigorous studies are needed to verify these findings.